"Everybody Makes Up Folksongs": Pete Seeger's 1950s College Concerts and the Democratic Potential of Folk Music. Issue 4 (November 2018) - BLAKE, DAVID
Abstract: During the 1950s, while blacklisted from the music industry and investigated by the House Un-American Activities Committee, Pete Seeger performed at colleges and universities across the United States. Although these concerts were crucial to his political work during the decade—Seeger repeatedly called them "the most important job I ever did in my life"—they have been neglected in scholarship. This article positions Seeger's campus concerts as crucial sites for demonstrating the democratic potential of folk music. Seeger sought to teach his audiences that folk music was an everyday activity created by people around the world, as well as an inherently participatory genre that could model civic cooperation. The democratic and educational purposes of his concerts marked a change from the labor advocacy of his 1940s work, and reflected ideas that he was then promulgating in his Sing Out! columns and Folkways Records. This essay examines his appearance at Cornell University on December 6, 1954 to illustrate three dimensions of Seeger's conception of democracy: audience participation, pluralistic repertoire, and rejection of the music industry. While illustrating Seeger's political actions, the Cornell concert also surfaces a tension between democratic participation and the class dynamics inherent in performing folk music for collegiate audiences.